"Trying to blend in, what else can we do?" Intergenerational relationships among aged inmates: Research. Issue 1 (2nd January 2019) - Filinson, Rachel; Ciambrone, Desirée
ABSTRACT: Aged inmates comprise a growing segment of the incarcerated population world-wide, yet very little research has been devoted to examining the intergenerational experiences of this cohort and the research that has been conducted has been inconsistent in its findings of victimization and negative social relationships. In an attempt to help fill this gap, this study examined the intergenerational elements of the lives of older (male) inmates and investigated their social supports and the degree of age segregation characterizing their carceral experience. Qualitative data revealed ruptured connections among inmates and their children and apprehensive relationships with younger fellow inmates or the correctional staff. Nevertheless, the findings counter the contention that the intergenerational environment is detrimental to aged inmates and that age-segregated carceral units would be beneficial to them.